Relationship between emotion regulation strategies and total conviction in promoting behavior change - Shigematsu, Jun; Kobayashi, Ryota (Frontiers in Psychology, 2022)
Research conducted in the recent past have proposed total conviction as a factor associated with cognitive reappraisal that may produce changes in emotion and behavior. However, the factors that influence total conviction are not yet clearly identified. In this study, we focused on daily emotion regulation strategies and examined the relationship between emotion regulation strategies and total conviction. A total of 42 undergraduate and graduate students participated in this study. They measured their tendency toward daily emotion regulation strategies and then engaged in the cold pressor task (CPT) which is a distress tolerance task. Participants were then presented with information that encouraged them to engage in the task while enduring distress, creating a context for cognitive reappraisal of the task. Thereafter, they engaged in a second CPT. Finally, the degree of total conviction to the information that prompted reappraisal was measured. The results showed that total conviction in the experimental situation predicted behavior change. We found that the tendency to use routine cognitive reappraisal was not associated with total conviction, while the tendency to use expressive suppression would have a negative effect on total conviction. Furthermore, the expressive suppression tendency was found to moderate the relationship between total conviction and behavior change. These results indicate that the occurrence of total conviction in cognitive reappraisal leads to behavior change, though the tendency toward daily cognitive reappraisal is not related to the occurrence of total conviction in the experimental setting. The results also suggest that daily expressive suppression inhibits total conviction, particularly in situations where cognitive reappraisal is required.